2018
DOI: 10.1177/1557988318803505
|View full text |Cite
|
Sign up to set email alerts
|

Role of Psychosocial Job Stressors on Sexual Function of Male Nurses: The Mediator Role of Work Ability

Abstract: There is limited information on the specific psychosocial risks at work that can impact sexual function. The general aim of this study was to investigate the effects of multiple dimensions of psychosocial work stressors on the male sexual function. This was a cross-sectional study conducted among 153 male nurses working in two hospitals in Iran. Sexual function and psychosocial job stressors were measured using the Persian version of the International Index of Erectile Function (P-IIEF) and the Persian version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
4
0
5
Order By: Relevance
“…( 5) Issue( 4) Part (1) (2020( medical group disagreed, while 30% of the nonmedical group disagreed. The results of the medical group came in agreement with Mokarami et al, who concluded that job stress, lack of clear job roles and high job demands could affect the sexual function of male nurses and Bekhbat and Neigh, said that stress can cause men to have a busy, frazzled mind and distract them from wanting sex or being present during sex and it can also influence mood, leading to anxiety and depression, which can diminish libido in their own right [31,32].…”
Section: Discussionsupporting
confidence: 83%
“…( 5) Issue( 4) Part (1) (2020( medical group disagreed, while 30% of the nonmedical group disagreed. The results of the medical group came in agreement with Mokarami et al, who concluded that job stress, lack of clear job roles and high job demands could affect the sexual function of male nurses and Bekhbat and Neigh, said that stress can cause men to have a busy, frazzled mind and distract them from wanting sex or being present during sex and it can also influence mood, leading to anxiety and depression, which can diminish libido in their own right [31,32].…”
Section: Discussionsupporting
confidence: 83%
“…The results of a recent study suggested that work schedule and occupational stressors had a a significant relationship with sexual satisfaction. [ 29 ] It can be stated that government employees have regular work schedule and more job stability, which can cause higher sexual satisfaction. Satisfaction with married life was another factor with a significant relationship with sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…WAI examines the ability to work in seven dimensions and the final score is the sum of the seven scores and is in the range of 7–49. A WAI score below 36 is classified as inappropriate or inadequate, and a WAI ≥ 37 is classified as appropriate [ 21 ]. It is assumed that people with poor performance scores have a lower mean MRADL score than people with appropriate work ability scores [ 2 ].…”
Section: Methodsmentioning
confidence: 99%